Knowledge, beliefs, attitudes and habits in relation to home delivery - Paredes, Luis (2015)
OBJECTIVES: To identify, beliefs, attitudes, knowledge and practices that limit the accessibility to the institutional delivery. DESIGN: Operational research, qualitative. MATERIALS AND METHODS: Women of childbearing age who live in peri-urban and rural areas of Rioja. The sampling of the population was non-probability of accidental type. RESULTS: The protestors consider pregnancy as a normal event, with no impact on their activities. Delivery care takes place outside of a health institution in the not necessarily conditioned environment, with a share of the husband or mother. Delivery is preferred squatting or kneeling position. Women see health services do not respect their customs and in some cases abuse is added. If care establishment, care provider is preferred by women. economic factors and geographic accessibility are identified. CONCLUSIONS: Acceptance of hospital births in the study population is limited by cultural, economic and geographical factors. In some cases there is recognition of the benefits. Health services must take into account the perceptions of users for better service.